Psychoanalytical Considerations of Emotion Regulation Disorders in Multiple Complex-Traumatized Children—A Study Protocol of the Prospective Study MuKi - Hug, Felicitas; Degen, Tom; Meurs, Patrick; Fischmann, Tamara (Frontiers in Human Neuroscience, 2022)
Studies in adults with mental disorders suggest that the experience of early and chronic trauma is associated with changes in reward expectancy and processing. In addition, severe childhood trauma has been shown to contribute to the development of mental disorders in general. Data on effects of early childhood trauma on reward expectancy and processing in middle childhood currently appear insufficient. The present study aims to fill this research gap by examining the effects of developmental trauma disorder (DTD) on reward expectancy and processing in children aged eight to twelve years, testing the hypothesis that children with multiple complex traumas exhibit altered reward processing as a result of prior disappointing reward experiences. One main feature of developmental trauma disorder is early experiences of multiple separation from important and close relationships alongside other experiences of emotional or physical harm. In the sequel children often show affect regulation disorders. To investigate this, we have developed an adapted version of the Monetary Incentive Delay (MID) Task, which examines children's expectation of reward or frustration. In this first study, behavioral data will be collected from N=40 children (n=20 experimental group and n=20 healthy controls) using this adapted version of the MID Task. Children in the experimental group will be recruited from youth welfare centers in Frankfurt a.M., Germany. Healthy control subjects will be recruited from after-school-care facilities. A brief trauma screening will be conducted for both groups, experimental and control. If children show signs of trauma, the presence of a developmental trauma disorder will be further delineated by a German translation of the Developmental Trauma Disorder Structured Interview for Children (DTDSI-C) which was translated the first time in German by our research group. We hypothesize that children in the experimental group will be less accurate in performing the Monetary Incentive Delay Task because of their impaired emotion regulation skills due to emotional avoidance following developmental trauma. If the results of our initial behavioral study are promising, the MID task will be used in a future study to elucidate the relationship between trauma developmental disorder, reward expectancy and processing, and neurobiological processes in middle childhood.